Imaging the stomatal physiology of somatic embryo-derived peanut leaves by scanning electrochemical microscopy - Parthasarathy, Meera; Singh, Shweta; Hazra, Sulekha; Pillai, Vijayamohanan K. (Analytical and Bioanalytical Chemistry, 2008)
The stomatal physiology, chlorophyll distribution and photosynthetic activity of somatic embryo (SE)- and seedling-derived peanut plants grown in vitro (test tube-grown) and extra vitrum (soil-grown) are investigated using scanning electrochemical microscopy (SECM). This SECM imaging is performed in two different feedback modes, corresponding to oxygen evolution and chlorophyll distribution. More specifically, the oxygen evolution profiles of the in vitro leaves indicate important differences in leaf anatomy between the SE- and seedling-derived leaves. On the other hand, the chlorophyll distribution images show individual stomata of size ca. 27 +/- 5 mu m. Further studies on senescing (aged) leaves reveal interesting voltammograms that vary widely over the stomatal complexes and the surrounding tissues, probably due to the release of electroactive metabolites during chlorophyll breakdown when the leaves turn yellow. Thus, the present investigation could open up new opportunities for characterizing botanical systems using electroanalytical techniques. In addition, it could provide further insights into various areas of current relevance, including signal transduction, cell fate/differentiation and developmental biology.
Keywords: leaf senescence; oxygen evolution; photosynthesis; SECM; somatic embryogenesis; stomata

Invertase inhibition based electrochemical sensor for the detection of heavy metal ions in aqueous system: application of ultra-microlelectrode to enhance sucrose biosensor's sensitivity - Bagal-Kestwal, Dipali; Karve, Meena S.; Kakade, Bhalchandra A.; Pillai, Vijayamohanan K. (Biosensors & Bioelectronics, 2008)
We are reporting fabrication and characterization of electrochemical sucrose biosensor using ultra-microelectrode (UME) for the detection of heavy metal ions (Hg(II), Ag(I), Pb(II) and Cd(II)). The working UME, with 25 mu m diameter, was modified with invertase (INV, EC: 3.2.1.26) and glucose oxidase (GOD, EC: 1.1.3.4) entrapped in agarose-guar gum. The hydrophilic character of the agarose-guar gum composite matrix was checked by water contact angle measurement. The atomic force microscopy (AFM) images of the membranes showed proper confinement of both the enzymes during co-immobilization. The dynamic range for sucrose biosensor was achieved in the range of 1 x 10(-10) to 1 x 10(-7) M with lower detection limit 1 x 10(-10) M at pH 5.5 with 9 cycles of reuse. The spectrophotometric and electrochemical studies showed linear relationship between concentration of heavy metal ions and degree of inhibition of invertase. The toxicity sequence for invertase using both methods was observed as Hg(2+) > Pb(2+) > Ag(+) > Cd(2+). The dynamic linear range for mercury using electrochemical biosensor was observed in the range of 5 x 10(-10) to 12.5 x 10(-10) M for sucrose. The lower detection limit for the fabricated biosensor was found to be 5 x 10(-10) M. The reliability of the electrochemical biosensor was conformed by testing the spike samples and the results were comparable with the conventional photometric DNSA method. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Co-immobilization; Electrochemical biosensor; Heavy metal ions; Invertase (INV)-glucose oxidase (GOD); Mercury; Ultra-microelectrode (UME)

Imaging hydrogen oxidation activity of catalyst-coated perfluoro sulfonic acid-polymer electrolyte membranes using scanning electrochemical microscopy - Parthasarathy, Meera; Pillai, Vijayamohanan K. (Journal of Chemical Sciences, 2009)
Scanning Electrochemical Microscopy (SECM) is a unique technique for studying fast heterogeneous kinetics and to map reactivity gradients along the surface of an electrocatalyst, especially when it involves multiple surface sites of varying reactivity. It combines the dual advantages offered by ultramicroelectrode (UME) voltammetry in terms of reduced ohmic drop and insignificant double layer charging contribution with the advantages of imaging by rastering the UME across an electro-active surface. In this work, we demonstrate these distinctive features of SECM in evaluating reactivity gradients on catalyst (Pt/C) coated NafionA (R) films towards hydrogen oxidation activity, a reaction of immense technological relevance. Imaging has been performed in the feedback mode by allowing H(2) evolution at the tip (25 A mu m Pt UME), which is reoxidized at the substrate electrode containing Pt/C-Nafion film. Interesting distribution in H(2) oxidation activity has been observed as a function of potential applied to the Pt/C-Nafion film. In addition, a plot of normalized tip current versus the substrate electrode potential indicates the effect of potential-induced reactivity change in the catalyst-coated membranes. The results of the present investigation are believed to be useful to H(2)/O(2) PEM fuel cells with respect to evaluating reactivity gradients of catalyst-coated polymer electrolyte membranes, which is important to rectify problems related to catalyst utilization.
Keywords: hydrogen oxidation; Imaging; Nafion; platinum; SECM

Improved performance of phosphonated carbon nanotube-polybenzimidazole composite membranes in proton exchange membrane fuel cells - Kannan, Ramaiyan; Kagalwala, Husain N.; Chaudhari, Harshal D.; Kharul, Ulhas K.; Kurungot, Sreekumar; Pillai, Vijayamohanan K. (Journal of Materials Chemistry, 2011)
Development of thermally stable polymer electrolyte membranes with higher proton conductivity as well as mechanical stability is a key challenge in commercializing PEM fuel cells operating above 100 degrees C. Polybenzimidazole membranes are one of the promising candidates in this category although with limited mechanical stability and moderate proton conductivity. Here the incorporation of functionalized MWCNT is shown to increase both these key parameters of the polybenzimidazole membranes. Further, formation of a domain like structure after the incorporation of phosphonated MWCNTs (P-MWCNTs) in phosphoric acid doped polybenzimidazole membranes is demonstrated. The enhanced performance has been attributed to the formation of proton conducting networks that formed along the sidewalls of P-MWCNTs with a domain size of 17 nm as estimated from the small angle X-ray scattering measurements. Membrane electrode assembly (MEA) impedance measurements further reveal that the activation energy of oxygen reduction reaction (ORR) reduced for the composite membranes with enhanced proton conductivity. In addition, the mechanical strength measurements reveal a significant improvement in the yield strength and ultimate strength. Also, the mechanical strength of the composite membrane has been increased significantly as indicated by the improvement in the ultimate strength from 65 MPa to 100 MPa for the pristine and composite membranes, respectively. The optimum loading of P-MWCNTs is found to be 1% as inferred from the polarization measurements carried out using pure hydrogen and oxygen. Thus, this study provides a unique opportunity to tune the properties of polymer electrolytes to prepare application oriented hybrid membranes using CNTs with tailor-made functional groups.

In situ electrochemical organization of CdSe nanoclusters on graphene during unzipping of carbon nanotubes - Debgupta, Joyashish; Shinde, Dhanraj B.; Pillai, Vijayamohanan K. (Chemical Communications, 2012)
In situ decoration of very small CdSe quantum dots on graphene nanoribbons (GNRs) has been achieved during the electrochemical unzipping of single walled carbon nanotubes. Critical parameters like the width of the GNRs, size distribution of quantum dots and their organization on GNRs have been shown to be strongly dependent on the electric field and time.